The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.12783/dtem/iceme-ebm2016/4127
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Interaction of China’s Knowledge-Intensive Business Services and Manufacturing Upgrading

Abstract: KIBS is a kind of advanced production factor which could increase the added value and the productivity of manufacturing in the global value chain by industry association effect. This paper empirically tests the dynamic relationship between KIBS and manufacturing upgrading by VAR model. The results show that there is a long-term dynamic equilibrium and causal relationship between KIBS and manufacturing. The positive effect of the former on the latter is obvious and long-lasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Within the service industry, knowledge-intensive business services (KIBS) demonstrate particularly high growth rates, including in developing countries [Janger et al, 2017]. In China, the added value created in KIBS industries grew more than fivefold between 2004 and 2014 [Fang et al, 2016]. KIBS rank among the most innovative sectors in the European Union's Community Innovation Survey (CIS).…”
Section: Resultsmentioning
confidence: 99%
“…Within the service industry, knowledge-intensive business services (KIBS) demonstrate particularly high growth rates, including in developing countries [Janger et al, 2017]. In China, the added value created in KIBS industries grew more than fivefold between 2004 and 2014 [Fang et al, 2016]. KIBS rank among the most innovative sectors in the European Union's Community Innovation Survey (CIS).…”
Section: Resultsmentioning
confidence: 99%
“…Zhou, Kautonen and Wei (2015) reported that innovation activity in Chinese manufacturing firms became more intensive when they simultaneously used services from KIBS companies specialised in R&D, IT, marketing and management consultancy. Similarly, Wei and Zhou (2016) and Fang, Zhao and Zhang (2016) reported that KIBS inputs enhanced innovation activity in Chinese manufacturing. Moreover, this effect also occurs if one restricts the analysis to the sample of small and medium-sized manufacturing enterprises (Zhou, Kautonen, Wang & Wang, 2017).…”
Section: Kibs In Silk Road Countriesmentioning
confidence: 89%